PENGARUH KOMPETENSI PEDAGOGIK DOSEN AKUNTANSI DAN PROFESIONALISME DOSEN AKUNTANSI TERHADAP MOTIVASI BELAJAR MAHASISWA AKUNTANSI (Studi Tentang Persepsi Mahasiswa Akuntansi di Universitas Pamulang Tahun Akademik 2015/2016) - Yulyanah Yulyanah (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
AbstractThe purpose of this study was to determine how to student's perception about the pedagogical competence of accounting lecturer in the learning process, whether there is significant influence between the pedagogic competence of accounting  lecturer and professioalism of accounting lecturer with learning motivation accounting student at the Pamulang University in academic year 2015/2016. This research uses descriptive method that involved 169 respondent by using questionnaires. Analyzed using a statistical simple regression analysis  (SPSS V.23). Result showed that the variables (pedagogical competence of accounting lecturer and professioalism of accounting lecturer) simultaneously positive effect on learning motivation. Keywords: pedagogical competence, professionalism, learning motivation